Frequency of Worms Infestation in Adult Anemic Patients (Medical Forum Monthly, 2020)
Objective: Among other causes, worm infestation is a common yet usually overlooked in the developing countries. Therefore the purpose of this study was to know its frequency among the anemic patients.Study Design: Descriptive case series studyPlace and Duration of Study: This study was conducted at Department of Medicine, Ayub Teaching Hospital Abbottabad from March 2018 to September 2018.Materials and Methods: Through non-probability consecutive sampling technique, a sample of 215 patients was observed by using Expected Prevalence7: 5.3%, Confidence Level: 95%, Absolute Precision: 3%.Results: Out of 215 patients, 40% were males while female patients were 60%. Mean ± SD of age was 29 ± 2.77. More over the frequency of worm infestation was found to be 48% percent.Conclusion: The frequency of worms infestation in our study was found to be forty eight percent of adult patients with anemia in our setup.